From Grants to Loans: Nepal’s Shifting Aid Architecture and Its Macroeconomic Implications (Research Nepal Journal of Development Studies, 2025)
This study provides a comprehensive, twenty-year analysis of Nepal’s transformation in development finance, documenting a pronounced shift from grant-based aid to loan dominated assistance between fiscal years 2003/04 and 2023/24. Drawing on annual fiscal data from the Government of Nepal’s Economic Surveys (2004–2025), the research employs time-series analysis to chart evolving patterns in aid composition, disbursement efficiency, external debt levels, and the share of capital expenditure financed by foreign resources. Grounded in dependency theory (Escobar, 1992) and post-development critique (Escobar, 2012), the study interrogates how loan reliance may perpetuate structural imbalances. It also engages the capabilities approach (Sen, 1999; Nussbaum, 2011), arguing that development success must be measured by expanded freedoms rather than mere financial inflows. Recent scholarship on emerging donor influence (Nishio, 2024) contextualizes Nepal’s entanglement with new financiers such as China’s AIIB and BRICS development banks while Fitriani’s (2024) work on institutional capacity highlights governance constraints that mediate aid effectiveness. The findings reveal a steep decline in grant share from over 90% in 2003/04 to under 20% by 2023/24 concurrent with a rise in loan commitments that have lifted the loan-to-GDP ratio to over 4%. These trends coincide with higher repayment obligations and pressures on fiscal space, underscoring the urgent need for strategic borrowing policies, robust debt-management frameworks, and strengthened transparency and oversight mechanisms to safeguard sustainable development outcomes.